2014
DOI: 10.18632/aging.100652
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatic CD36 expression with age is associated with enhanced susceptibility to nonalcoholic fatty liver disease

Abstract: CD36 has been associated with obesity and diabetes in human liver diseases, however, its role in age-associated nonalcoholic fatty liver disease (NAFLD) is unknown. Therefore, liver biopsies were collected from individuals with histologically normal livers (n=30), and from patients diagnosed with simple steatosis (NAS; n=26). Patients were divided into two groups according to age and liver biopsy samples were immunostained for CD36. NAFLD parameters were examined in young (12-week) and middle-aged (52-week) C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 40 publications
(62 reference statements)
8
64
1
Order By: Relevance
“…Despite the well-documented function of CD36 in fatty acid uptake (41) and several reports that associate hepatic CD36 signaling with an increased risk of developing liver steatosis (3,5,6,8,42), we showed that overexpression of CD36 in the livers of our transgenic mice did not worsen metabolic functions but rather protected the mice from the detrimental metabolic changes caused by HFD feeding and prolonged fasting. The antisteatotic effect of CD36 is consistent with a report that whole-body CD36 ablation exacerbated hepatic steatosis in the ob/ob background (10) but is contrary to a recent study showing that liver-specific knockout of CD36 reduced the liver lipid content when mice were challenged with HFD (42).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Despite the well-documented function of CD36 in fatty acid uptake (41) and several reports that associate hepatic CD36 signaling with an increased risk of developing liver steatosis (3,5,6,8,42), we showed that overexpression of CD36 in the livers of our transgenic mice did not worsen metabolic functions but rather protected the mice from the detrimental metabolic changes caused by HFD feeding and prolonged fasting. The antisteatotic effect of CD36 is consistent with a report that whole-body CD36 ablation exacerbated hepatic steatosis in the ob/ob background (10) but is contrary to a recent study showing that liver-specific knockout of CD36 reduced the liver lipid content when mice were challenged with HFD (42).…”
Section: Discussioncontrasting
confidence: 93%
“…The hepatic expression of CD36 is under the transcriptional control of the nuclear receptors: liver X receptor (LXR), pregnane X receptor (PXR), peroxisome proliferator-activated receptors (PPARs), and the aryl hydrocarbon receptor (AhR) (4). Some studies have suggested that hepatic CD36, by functioning as a fatty acid transporter, has a role in the pathogenesis of hepatic steatosis (3), obesity (7,8), and age-related hepatic steatosis (5). Furthermore, we and others reported that induction of CD36 was a common factor in fatty liver following the activation of LXR and PXR (6,9).…”
mentioning
confidence: 99%
“…A recent study reported that increased hepatic CD36 expression with age is associated with enhanced hepatic fat uptake and increased susceptibility to NAFLD (Sheedfar et al 2014). Meanwhile, in another study, HFD-induced obesity primes inflammation in adipose tissue prior to development of hepatic inflammation (van der Heijden et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been limited data available regarding the differential effect of HFD feeding on the progression of NAFLD and/or renal injury, a few papers have been published on these topics recently (Sheedfar et al 2014;van der Heijden et al 2015a). A recent study reported that increased hepatic CD36 expression with age is associated with enhanced hepatic fat uptake and increased susceptibility to NAFLD (Sheedfar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Powdered tissue was homogenized as described previously. 25 Equal amounts of protein were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, transferred to PVDF membrane (Amersham, Buckinghamshire, UK) and the resulting immune complex was visualized using the Molecular Imager ChemiDoc XRS+System (Bio-Rad, Veenendaal, The Netherlands). Antibodies against phospho-and total AKT were purchased from Cell Signaling (Leiden, The Netherlands).…”
Section: Immunoblot Analyses In Micementioning
confidence: 99%